Qualidade fisiológica de sementes de Brachiaria e avaliação da produtividade de massa seca em diferentes sistemas de integração lavoura-pecuária sob irrigação - Pariz, Cristiano Magalhães [UNESP]; Ferreira, Roberta Leopoldo; De Sá, Marco Eustáquio [UNESP]; Andreotti, Marcelo [UNESP]; Chioderoli, Carlos Alessandro [UNESP]; Ribeiro, Ana Paula [UNESP] (FapUNIFESP (SciELO), 2010)
The speed and magnitude of tropical pastures expansion in Brazil are related to the availability of quality seeds. This research aimed to evaluate the physiological quality of seeds of two Brachiaria species submitted to germination and viability tests and also estimate, for both species, the fresh and dry mass yield, under different irrigated crop-livestock integration systems. For field analysis, the experimental design was a randomized complete block, in subplots, with four intercrops in the plot (Brachiaria brizantha cv. Marandu and Brachiaria ruziziensis simultaneously established with corn and nitrogen fertilization coverage), and four forage cutting times, in the winter/spring season, in subplots, with four replications. In the laboratory, the experimental design was completely randomized, with four replications per treatment/test. The germination and viability tests indicated that B. brizantha seeds showed higher physiological quality, when compared with B. ruziziensis, while the tetrazolium test and germinated seedlings characteristics were similar. The B. ruziziensis, simultaneously intercropped with corn, was the less viable intercrop, due to the lower fresh and dry mass yield and litter deposition on the soil surface. In general, the pasture formation for the second season cultivation, intercropped with corn, was an excellent alternative for crop-livestock integration under a no-tillage system.
Physiological quality of Brachiaria seeds and dry mass yield estimate under different irrigated crop-livestock integration systems
Keywords: Accelerated aging; Controlled deterioration; Germination; Tetrazolium; Vigor; Brachiaria; Urochloa brizantha; Zea mays